Prognostic Impacts of D816V KIT Mutation and Peri-Transplant RUNX1–RUNX1T1 MRD Monitoring on Acute Myeloid Leukemia with RUNX1–RUNX1T1 - Cho, Byung-Sik (Cancers (Basel), 2021)
SIMPLE SUMMARY: Acute myeloid leukemia (AML) with RUNX1-RUNX1T1 is a heterogeneous disease entailing different prognoses. Patients with high-risk features can benefit from allogeneic hematopoietic stem cell transplantation (HSCT) or autologous HSCT. However, insufficient data about major risk factors, such as KIT mutations and measurable residual disease (MRD) status for relapse, make it difficult to clarify the benefit of each transplant strategy. Moreover, limited data are available to elucidate the exact prognostic impacts of different types of KIT mutations and optimal thresholds or time points for RUNX1–RUNX1T1 MRD assessment, particularly in the setting of HSCT. Given the lack of prospective study, the current retrospective study, including a large cohort of high-risk AML patients with RUNX1–RUNX1T1, firstly demonstrated the differentiated prognostic impact of D816V KIT mutation among various KIT mutations and clarified optimal time points and thresholds for RUNX1–RUNX1T1 MRD monitoring in the setting of HSCT. ABSTRACT: The prognostic significance of KIT mutations and optimal thresholds and time points of measurable residual disease (MRD) monitoring for acute myeloid leukemia (AML) with RUNX1-RUNX1T1 remain controversial in the setting of hematopoietic stem cell transplantation (HSCT). We retrospectively evaluated 166 high-risk patients who underwent allogeneic (Allo-HSCT, n = 112) or autologous HSCT (Auto-HSCT, n = 54). D816V KIT mutation, a subtype of exon 17 mutations, was significantly associated with post-transplant relapse and poor survival, while other types of mutations in exons 17 and 8 were not associated with post-transplant relapse. Pre- and post-transplant RUNX1–RUNX1T1 MRD assessments were useful for predicting post-transplant relapse and poor survival with a higher sensitivity at later time points. Survival analysis for each stratified group by D816V KIT mutation and pre-transplant RUNX1–RUNX1T1 MRD status demonstrated that Auto-HSCT was superior to Allo-HSCT in MRD-negative patients without D816V KIT mutation, while Allo-HSCT was superior to Auto-HSCT in MRD-negative patients with D816V KIT mutation. Very poor outcomes of pre-transplant MRD-positive patients with D816V KIT mutation suggested that this group should be treated in clinical trials. Risk stratification by both D816V KIT mutation and RUNX1–RUNX1T1 MRD status will provide a platform for decision-making or risk-adapted therapeutic approaches.